Lithiated azetidine and azetine chemistry - Pearson, CI (2014)
This work describes developments in new azetidine and azetine chemistry; specifically, methods developed for the introduction of functionality α- to nitrogen in both ring systems, with additionally in situ formation of the latter system, from azetidine substrates. Chapter 1 discusses the growing importance of azetidines, and the current methods available for making substituted azetidines by ring formation. Further discussion comprises of current sp3 C–H activation approaches α- to nitrogen in heterocyclic compounds as potential methods for sp3 C–H activation on azetidines to give substituted azetidines. Previous work by the Hodgson group in this area is detailed. Chapter 2 describes the advance made towards 2,3-disubstituted azetidines using the thiopivaloyl protecting/activating group, where the latter plays a key role. Optimisation, scope, selectivity and mechanistic insight into the α-deprotonation–electrophile trapping of a 3-hydroxy azetidine system is discussed, which successfully gives access to a range of 3-hydroxy-2-substituted azetidines. Preliminary investigations with 3-alkyl-2-substituted azetidines are also described. Chapter 3 describes the development of a straightforward protocol to make 2-substituted-2- azetines, a rarely studied and difficult to access 4-membered azacycle subclass, from readily accessible azetidine starting materials using α-deprotonation–in situ elimination followed by further α-lithiation–electrophile trapping. Extension of this methodology by transmetallation from the intermediate organolithium to the organocuprate, resulting in greater electrophile scope, is also described.